In silico analyses of heat shock protein 60 and calreticulin to designing a novel vaccine shifting immune response toward T helper 2 in atherosclerosis. (April 2017) - Karkhah, Ahmad; Saadi, Mahdiye; Nouri, Hamid Reza
Graphical abstract: Highlights: Fresh strategy are needed to fighting against atherosclerosis. Designing a novel multi-epitope vaccine to induce T helper 2 in atherosclerosis. The designed vaccine consists of several epitopes according to shock protein 60 and calreticulin. Binding of selected epitopes and adjuvant together by proper linkers in order to enhance the immunogenicity of vaccine. In silico analysis indicates that the designed vaccine is able to induce strong Th2 immune response in atherosclerosis. Abstract: Recent experiments demonstrated that atherosclerosis is a Th1 dominant autoimmune condition, whereas Th2 cells are rarely detected within the atherosclerotic lesions. Several studies have indicated that Th2 type cytokines could be effective in the reduction and stabilization of atherosclerotic plaque. Therefore, the modulation of the adaptive immune response by shifting immune responses toward Th2 cells by a novel vaccine could represent a promising approach to prevent from progression and thromboembolic events in coronary artery disease. In the present study, an in silico approach was applied to design a novel multi-epitope vaccine to elicit a desirable immune response against atherosclerosis. Six novel IL-4 inducing epitopes were selected from HSP60 and calreticulin proteins. To enhance epitope presentation, IL-4 inducing epitopes were linked together by AAY and HEYGAEALERAG linkers. In addition, helper epitopes selected from Tetanus toxin fragment C (TTFrC) were applied to induce CD4+ helper T lymphocytes (HTLs) responses. Moreover, cholera toxin B (CTB) was employed as an adjuvant. A multi-epitope construct was designed based on predicted epitopes which was 320 residues in length. Then, the physico-chemical properties, secondary and tertiary structures, stability, intrinsic protein disorder, solubility and allergenicity of this chimeric protein were analyzed using bioinformatics tools and servers. Based on bioinformatics analysis, a soluble, and non-allergic protein with 35.405 kDa molecular weight was designed. Expasy ProtParam classified this chimeric protein as a stable protein. In addition, predicted epitopes in the chimeric vaccine indicated strong potential to induce B-cell mediated immune response and shift immune responses toward protective Th2 immune response. Various in silico analyses indicate that this vaccine is a qualified candidate for improvement of atherosclerosis by inducing immune responses toward T helper 2.